5G wideband on‐chip dipole antenna for WSN soil moisture monitoring. Issue 4 (5th February 2021) - Elsheakh, Dalia; Shawkey, Heba
Abstract: Recently, soil dielectric constant detection has been used in the irrigation of vastly differing farming conditions. Soil monitoring has seen a push toward fifth generation (5G) telecommunications technology, due to the higher speed and bandwidth required to connect a huge number of sensor nodes simultaneously. A novel architecture for a fully integrated, unequal arms dipole antenna is presented in this article. The proposed on‐chip antenna is implemented using UMC180 nm CMOS technology. A dipole radiator is added on the upper metal layer, a ground sheet set at the lower metal layer and a patch layer is added on the intermediate metal layer. This configuration has improved the antenna impedance bandwidth by 38%. In addition, it increased the electrical length of the dipole antenna to reduce the antenna resonant frequency by 10 GHz. The proposed antenna has a total area 1300 × 250 μm, and its wide bandwidth extends from 21 to 40 GHz at reflection coefficient |S11 | < –7 dB, which makes it suitable for on‐chip wireless sensor network applications in 5G technology. All Simulations are completed by using the Ansys HFSS (high‐frequency structure simulator) ver.15 and the simulated results show a good comparison with measurements. To investigate the proposed antenna's performance in different environmental conditions, practical measurements for soil dielectric constant in different compositions with variable moisture ratios are applied. The resulting values are used in antenna simulation and have ultimately proved the antenna's improved capability to sense soil moisture in different conditions.